Theoretical perspectives on reproductive aging - Lee, Ronald; Chu, C. Y. Cyrus (Frontiers in Ecology and Evolution, 2023)
Age patterns of female reproduction vary widely among iteroparous animal species with determinate growth. Often fertility declines with age, but in other cases it may be flat across age or rising. Sometimes fertility ceases altogether, leaving a substantial postreproductive life span. In cooperative breeding species many females do not reproduce at all over their lifetimes or else may wait for a chance to breed as they grow older. Here we discuss theories that may provide some insights about how these diverse patterns might evolve. Then we present a simple optimal life history model and consider circumstances in which fertility might rise or fall with age. In our model, without assuming that costs per birth rise with age or that foraging efficiency declines, optimal fertility would tend to rise rather than decline because less energy would be allocated to survival at older ages. Fertility decline could arise in part from mutation accumulation, but Hamilton (1966) himself thought its role would be minor. Decline could derive from rising costs of fertility due to wear and tear on reproductive organs or foraging efficiency, but why does an organism not invest more in maintenance, repair and replacement? Fertility decline at older ages could also occur when an organism makes heavy intergenerational transfers to multiple offspring or grandoffspring, reducing resources for own reproduction. Forces tending to raise fertility with age include the declining share of energy allocated for survival at older ages, leaving more for fertility, an outcome strengthened by low extrinsic mortality. Another reason could be that after somatic growth ceases growth continues in knowledge and experience in energy acquisition and reproduction. Finally, in cooperative breeding groups females often achieve dominant status and become reproductive only at older ages. The balance of these and other forces determines age patterns of fertility and reproductive senescence. The weights on each of these forces will depend on other aspects of the life history and sociality of the species and perhaps on the environment as well. No single theoretical insight is likely to explain when reproductive senescence occurs.